Department of Environmental Affairs investigating the potential use of public private partnerships to fund green building initiatives : the case of the Department Of Environmental Affairs - Khoza, Shereen (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPA)--Stellenbosch University, 2021.